Phenomenological Studies Mother Gives Birth With Maryam’s Birth Model In The Independent Practice Of A Midwifer Mugi Rahayu Kalasan Sleman: Studi Lapangan Memperkuat Kompetensi Mahasisa Bidang Pemasaran - wina, winarsih; Nining Tunggal Sri Sunarti; Reni Tri Lestari (Jurnal Serambi Ilmu, 2024)
Labor or giving birth is one of the important events in human life. Normal childbirth is a gift for women from Allah Azza Wa Jalla. which has been recorded in the Qur’an through the experience of Siti Maryam, the mother of the Prophet Isa as., which is stated in Surah Maryam verses 22-26. Recently on social media, there has been a lot of discussion about Maryam’s birthing technique. According to Maryam Childbirth practitioner (PM) Mugi Rahayu, AmdKeb, SFil, MPH, this technique began to develop and become popular among mothers in 2012. The aim of the research was to phenomenologically describe mothers giving birth using the Maryam delivery model at PMB Mugi Rahayu Kalasan Sleman. The results of research on Maryam’s birth model in the independent practice of midwife Mugi Rahayu is a birth model that teaches pregnant women to understand and believe that childbirth is a religious event in the context of worshiping Allah SWT. In the implementation of Maryam’s birth, preparations began from the time she was pregnant, referring to 4 things implemented by pregnant women, namely: 1). Pregnant women “have to move” 2). Pregnant Women Never worry about pain 3). Pregnant women pay attention to nutrition, 4). Pregnant women are obliged to "seek knowledge" regarding women’s jurisprudence. As a health worker, you need to combine an approach with elements of faith and religious belief in all care from pregnancy, childbirth and postpartum. Keyword : Phenomenological Study, Maryam Method of Childbirth,